MUSIK BAMBU BANYUMAS - Saryoto, S.Kar., M.Hum. (Paraguna, 2018)
Bamboo  music  will not become  a musical identity  of an  area,  if it is  not related  to the inherent culture and  creativity  of the supporting community.  Likewise the  life of bamboo  music in Banyumas,  has  recently  experienced a change  when compared to several  decades before.  Therefore,  the presentation  of bamboo  music in Banyumas can  be  assumed to have  work  on  creativity   and  be  able  to  do  musical dialogue with  the  community,  so  that  their  lives  up  to now  still survive and  compete with other  types of  art.   To see  this,   a  multidisciplinary  approach  can  be  used  as  a paradigm  in observing it,  including  examining what  and  how  bamboo  music is  in Banyumas;  especially  those  related   to  the  culture  and  creativity  of  the  people. Bamboo   music   as   the   identity   of  the   Banyumas  community,   is   still  living   in accordance  with  the  dynamics  of the  supporting  community.  For this  reason,  it is necessary   to  examine    various  factors   that   support  this   bamboo    music   life, especially those  in the Banyumas cultural area.